Uppvärmning med spannmål och trädbränslen - Fredriksson, Carl; Sjölander, Johan (2005)
This examination work brings up opportunities to invest in a construction for heating with grain or pellets on farm level. As example we have chosen Fröberga Gård which is a farm located in Östergötland outside of Söderköping. The farm`s residential buildings is to day heated with oil and electricity. The result of our investigation shows that heating with grain is the best alternative, partly because of economical issues but also because you can grow the grain on your own farm and by that you can get better economy in your seed cultivation. To grow 16 tonne of grain as is needed demand gives a insignificant increase of work. Further an advantage is that no investment in machines is needed because all the machines witch is needed already is in use on the farm. In a situation where a new investment is needed as in the case we studied, is it often profitable to invest in a integrated furnace. Because all the components are well adapted to each other, and because that gives a high efficiency. If you already own a well working furnace is it often most profitable to connect a burner to it. It is important to know that heating with grain need more work than heating with pellets, because the high contents of ash in grain. Even if you choose pellets instead of grain the calculation shows good results. Because peat is an excellent but fairly untested raw material for pelletsproduction we have chosen to watch little more on its quality and conductions. We discovered that peat has a high heating value which makes it possible to raise the heat value in pellets through mix up peat and wood. Or you can make pellets with only peat and get a pellet with high heating value. Even the calculation with peatheating shows good results.